Analisis Yuridis Keabsahan Peralihan Hak Atas Surat Berharga (Studi Kasus Putusan Nomor 5/PDT.G/2018/PN SLT) - Gibran, Rizal Ananda; Avatar, Muhammad Raja; Hayatuddin, Raihan Ramadhan; Hendarwin, Rasendriya (Media Hukum Indonesia (MHI), 2025)
This research examines the validity of rights transfer over negotiable instruments based on the District Court Decision Number 5/Pdt.G/2018/PN Slt. The issue arose when a land certificate registered under the heir was transferred to another heir without mutual consent. The study aims to explain legal provisions regarding the transfer of negotiable rights and analyze judicial considerations in resolving the dispute. The research used a normative juridical method by reviewing legal documents. The findings revealed that the transfer was legally defective due to the absence of approval from all rightful heirs. The court ordered the reversion of ownership and declared the previous transfer legally invalid. The conclusion highlights that the validity of rights transfer must follow legal procedures and fairness principles